Campanula rotundifolia cytotype, distribution and first flowering dates ... - Wilson, J.; Perry, A.; Shepherd, JR.; Duran-Castillo, M.; Jeffree, CE.; Cavers, S. (NERC Environmental Information Data Centre, 2016)
This dataset comprises information of location and cytotype of over 1300 samples of Campanula rotundifolia L. from the northern hemisphere (mostly from Britain and Ireland) and data from a common garden study in which British and Irish cytotypes were grown together and their flowering phenology and growth were assessed. Campanula rotundifolia L. is a widespread polyploid perennial herbaceous plant, with diploid, tetraploid, pentaploid and hexaploid cytotypes. ... : Cytotype samples were collected by Centre for Ecology & Hydrology (CEH) or sent in by members of the public. The common garden study was conducted at CEH in Edinburgh. See supporting documentation for further information. ...